373. STRATEGIES ON OPTIMAL LYMPHADENECTOMY IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA: A RETROSPECTIVE ANALYSIS OF 1517 CASES IN A SINGLE CANCER CENTER. (24th September 2022) - Li, Kexun; Leng, Xue Feng; Du, Kunyi; Liu, Kun; He, Wenwu; Wang, Qifeng; Luo, Xi; Wang, Chenghao; Wang, Kangning; Liu, Guangyuan; Wei, Xing; Li, Haojun; et al.
Abstract: The incidence and mortality of esophageal cancer are high-ranking in the world in cancer, it is the forth primary cause of cancer-related death and has the sixth highest incidence rate in China. Our purpose is to discuss the impact of the number of lymph nodes dissection in esophagectomy for esophageal squamous cell carcinoma to patients' overall survival (OS), especially in the patients who have positive lymph nodes in recent years. Data were from the Sichuan Cancer Hospital & Institute Esophageal Cancer Case Management Database. We retrospective analyzed patients who underwent esophagectomy from Jan. 2010 to Dec. 2016. Patients were divided into two groups: Negative lymph nodes in the pathological results were assigned to N0 group, while patients with positive lymph nodes were divided into N+ group. The median number of resected lymph nodes (RLNs) during operation was 24, patients were assigned to group A/N0 and A/N+ according to RLNs number of 15–24, and number of RLNs more than 24 were assigned to group B/N0 and B/N+. After 62.8 months of median follow-up time, 1517 patients who received esophagectomy were included. In the N+ group, the median overall survival (OS) of N+ A group was 27.8 months (95% CI 23.8–31.8) compared to N+ B group was 33.3 months (95% CI 28.2–38.5). The OS at 1, 3, and 5 years were 80%, 40%, and 30% in the N+ A group, and there were 82%, 48%, and 35% in the N+ B group, respectively (P = 0.038 < 0.05). (HR 1.18, 95% CI 1.008–1.380, P = 0.038). Increasing the harvest of number of lymph nodes during surgery more than 24 could improve the OS of esophageal squamous cell carcinoma patients. It is demonstrated patients without lymph metastasis have a better OS than those with lymph metastasis. When we reached dissection more than 15 lymph nodes, there will be no more benefits in OS for further harvest of lymph node numbers. Patients with different stages may be given different lymph nodes dissection strategies.